Evaluating the benefits of adjuvant chemotherapy in patients with pancreatic cancer undergoing radical pancreatectomy after neoadjuvant therapy—a systematic review and meta-analysis - Wu, Jiahao; Zhang, Yike; Wang, Haodong; Guo, Wenyi; Li, Chengqing; Yu, Yichen; Liu, Han; Li, Feng (Frontiers in Oncology, 2024)
BackgroundMore and more patients with pancreatic cancer (PC) received neoadjuvant therapy (NAT) and then underwent radical pancreatectomy. However, the benefit of adjuvant chemotherapy (AC) for these patients is still controversial. This study is designed to determine the benefits of postoperative AC for patients with PC undergoing NAT and radical resection.MethodsWe conducted a comprehensive search of the PubMed, Embase, Web of Science, and Cochrane Library databases, covering the period from their inception until 10 September 2023. Our analysis focused on the assessment of overall survival (OS) and recurrence-free survival (RFS) through meta-analysis. The fixed-effects model and the random-effects model were used to process the data. Hazard ratios (HRs) and 95% confidence intervals (95% CIs) were employed to determine the necessary of administering AC for patients with PC who have undergone NAT and radical resection. We retrieved 3,063 search results, of which 3,048 were excluded because of duplication or after applying our inclusion and exclusion criteria.ResultsA total of 15 studies with 21,113 patients (7,794 patients in the AC group and 13,319 in the non-AC group) were included, all of which reported OS, and three studies reported disease-free survival (DFS)/tumor-specific survival (CSS)/RFS. The final results showed that AC significantly improved OS and DFS/CSS/RFS in patients with PC who underwent pancreatectomy after NAT [OS: HR = 0.80, 95% CI (0.75∼0.86), P < 0.00001, I2 = 48%; DFS/CSS/RFS: HR = 0.53, 95% CI (0.41~0.69), P < 0.00001, I2 = 0%]. Furthermore, we performed subgroup analyses and demonstrated that AC provided a significant survival benefit for patients with PC after NAT and resection regardless of the tumor size [<2-cm subgroup: HR = 0.72, 95% CI (0.5∼0.94), P = 0.01; ≥2-cm subgroup: HR = 0.79, 95% CI (0.65∼0.96), P = 0.02] and the margin status [R0 subgroup: HR = 0.83, 95% CI (0.77∼0.88), P < 0.00001; R2 subgroup: HR = 0.75, 95% CI (0.61∼0.92), P = 0.007]. AC also benefited the patients with a stage N0 [HR = 0.79, 95% CI (0.74~0.84), P < 0.00001], N1 [HR = 0.78, 95% CI (0.72∼0.85), P < 0.00001], or poorly/undifferentiated tumor [HR = 0.76, 95% CI (0.66∼0.87), P < 0.0001] in survival but not in patients with a stage N2 [HR = 0.69, 95% CI (0.43∼1.09), P = 0.11] or well/moderately differentiated tumor [HR = 0.97, 95% CI (0.66∼1.42), P = 0.87].ConclusionsAlthough AC showed survival benefit for patients with PC undergoing radical pancreatectomy after NAT, we still need to consider the lymph node stage and the degree of differentiation of the tumor when we gave AC to a patient. High-quality prospective randomized controlled studies are required to well disclose the value of AC in patients with PC undergoing radical pancreatectomy after NAT.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/ PROSPERO, identifier CRD42023461365.